Offshore baseline for the sheltered Eastern Chukchi Sea, Alaska coastal region (Point Barrow to Icy Cape) generated to calculate shoreline change rates - Gibbs, Ann E.; Ohman, Karin A.; Coppersmith, Ryan; Richmond, Bruce M. (USGS Science Data Catalog, 2017)
This dataset includes a reference baseline used by the Digital Shoreline Analysis System (DSAS) to calculate rate-of-change statistics for the sheltered north coast of Alaska coastal between Point Barrow and Icy Cape for the time period 1947 to 2012. This baseline layer serves as the starting point for all transects cast by the DSAS application and can be used to establish measurement points used to calculate shoreline-change rates.